2012
DOI: 10.2337/dc12-0493
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural White Matter Abnormalities and Cognitive Functioning in Type 2 Diabetes

Abstract: OBJECTIVETo examine whether type 2 diabetes is associated with microstructural abnormalities in specific cerebral white matter tracts and to relate these microstructural abnormalities to cognitive functioning.RESEARCH DESIGN AND METHODSThirty-five nondemented older individuals with type 2 diabetes (mean age 71 ± 5 years) and 35 age-, sex-, and education-matched control subjects underwent a 3 Tesla diffusion-weighted MRI scan and a detailed cognitive assessment. Tractography was performed to reconstruct several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
175
4
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 38 publications
15
175
4
6
Order By: Relevance
“…Our investigation provides novel insight into the neuropathological effects of WM integrity reduction on cognition in T2DM. FA and MD are the primary DTI-derived metrics believed to reflect overall WM health, maturation, and organization (15,16). In addition to these primary DTI measures, l 1 , which reflects axon integrity, and l 23 , which reflects myelin sheath integrity, can be useful in understanding the underlying physiology (8,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our investigation provides novel insight into the neuropathological effects of WM integrity reduction on cognition in T2DM. FA and MD are the primary DTI-derived metrics believed to reflect overall WM health, maturation, and organization (15,16). In addition to these primary DTI measures, l 1 , which reflects axon integrity, and l 23 , which reflects myelin sheath integrity, can be useful in understanding the underlying physiology (8,29).…”
Section: Discussionmentioning
confidence: 99%
“…Fractional anisotropy (FA) and mean diffusivity (MD) describe fiber density, axonal diameter, and myelination in WM based on quantitative measure of the degree of diffusion anisotropy (15,16). As reported previously based on the DTI technique, decreased FA or increased MD in varieties of cognitive dysfunction related to Alzheimer disease (AD) (17,18), amnestic mild cognitive impairment (MCI) (19), schizophrenia (20,21), and type 1 diabetes (22), etc.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with current theories about the localization of higher cognitive functions. Interestingly, diffusion alterations have also been observed in patients with diabetes who performed cognitively similar to control subjects (39,40) and in individuals with the metabolic syndrome (42), suggesting that diabetesassociated white matter abnormalities occur early in the disease process.…”
Section: Type 2 Diabetesmentioning
confidence: 93%
“…Most studies observed a global decrease in FA or increase in MD that could not be explained by differences in vascular lesion load or total brain volume (32,(39)(40)(41). Disruption of white matter connections in the temporal lobe was specifically associated with decreased memory performance (39,41), whereas increased MD in frontal and temporal and posterior fiber tracts was related to reduced information processing speed (39).…”
Section: Type 2 Diabetesmentioning
confidence: 99%